The Constitutional Model Family, The Sexual Orientation of Parents and The Rights of The Child - Plácido Vilcachagua, Álex Fernando (2015)
Today it is found that heterosexual marriage and cohabitation and do not identify the family, but a particular type of family as an option means among other possible. International treaties recognize that the right to establish a family is expressly referred to the person regardless of their gender or sexual orientation. There is no reception inconstitutional homosexual cohabitation as a family type but must be stated that the choice of the legislator is to recognizes a marriage or no.